Auricular Vagus Nerve Stimulation Improves Chronic Pain and Pain-Related Cytokine Levels: A Clinical Study - James Anderson; Forest Tennant (International Journal of Pain Management, 2023)
Periauricular Vagus Nerve Stimulation (pVNS) has been proven safe and effective in reducing chronic pain and related comorbidities in numerous clinical studies. This multicenter, interventional study used a non-randomized, interrupted time-series analysis to test the efficacy of an 8-week treatment protocol using the Stivax neurostimulator device. Subjects (n=33, 15 F, 18 M, age 40-77) were recruited at 3 clinic sites in California and Colorado. All subjects had long-term chronic pain and had failed other treatments. Subjects were treated with the Stivax device 3 times (2 weeks on, 1 week off). Subjective assessments of pain (Visual Analog Scale), disability (Oswestry Disability Index), depression (PHQ-9), and activity (IPAQ-E) were collected at baseline and weekly. Objective blood levels of pain-related cytokines collected at the end of weeks 2 and 8. Most subjects reported reduced pain, disability, and depression, with increased activity levels. At the end of week 8, subjects reported an average reduction in pain by 38.5% (3 subjects reported no pain), depression by 43.6% (2 subjects reported no depression), disability by 38.6% (2 subjects reported no disability), and an average 26.1% increase in activity level (5 subjects doubled their activity level). Levels of the pain-related cytokines IL-1ꞵ, IL-2, IL-3, IL-7, IL-10, IL-15, IL-17α, IL-21, TNF-α, IFN-γ, and FLT3-ligand showed improvement at week 8. pVNS is believed to “reset” central sensitization underlying chronic pain and other central sensitization syndromes, engaging the body’s pain modulation systems. Our results indicate that pVNS can clinically significantly improve chronic pain and associated morbidities without adverse effects.
Keywords: Chronic pain